Comprehensive obstetric care with oxytocin massage on mrs. M for increased breast milk production in postpartum mothers - Jesi miranda; Enderia Sari (Jurnal Inspirasi Kesehatan, 2023)
Background: Breast milk is the best food for newborns and is the only healthy food a baby needs in the first month of life. However, not all mothers can exclusively breastfeed their babies. One of the main obstacles for a mother in breastfeeding is because milk production is not smooth. The way that can be done to facilitate breast milk production is to do oxytocin massage. Objective: Carry out obstetric care for Mrs. M which includes obstetric care for pregnancy, childbirth, puerperium, and neonates comprehensively and to determine the effect of oxytocin massage during the puerperium to increase breast milk production in postpartum mothers. Method: The method used is a case study and assesses the effect of oxytocin massage performed on Mrs. M with data collection techniques through interviews, observation, physical examination, documentation studies, literature studies, and giving questionnaires to patients before and after oxytocin piat. Results: After comprehensive obstetric care during pregnancy, childbirth, puerperium and neonates in Mrs. M with oxytocin massage for 15 minutes for 6 consecutive days there was an increase in breast milk production in postpartum mothers. Conclusion: The obstetric care that has been given to Mrs. M with oxytocin massage is useful in increasing breast milk production.